The state of the microbiota of the respiratory tract in patients with tuberculosis of the respiratory system: literature review - S. I. Kayukova; I. A. Vasilyeva; N. S. Mironov; E. A. Gugueva; T. I. Sharkova; M. V. Sinitsyn (Acta Biomedica Scientifica, 2025)
Background. Tuberculosis is one of the leading infectious diseases that claim millions of lives every year. In the Russian Federation, over the past 10 years, there has been a steady decrease in the incidence and mortality from tuberculosis. The effectiveness of the treatment of respiratory tuberculosis depends on the genetics and immunology of the host, environmental factors, drug resistance of the pathogen (MDR/XDR), the presence of concomitant comorbid pathology (TB/HIV). However, the state of the microbiota continues to be poorly studied, but an important factor. The aim. To study the data of the world literature on the state of microbiocenosis of the respiratory tract in patients with tuberculosis of the respiratory system. Methods. The search and analysis of literary sources in international and domestic databases (Google Scholar, PubMed, eLibrary) for the period 2018–2023 were carried out. Discussion. To assess the microbiota of the respiratory tract, the 16s sequencing method of studying the species diversity of microorganisms is most successfully used. It has been proven that a violation of the microbiocenosis of the respiratory tract, namely the formation of dysbiosis against the background of persistent tuberculosis infection, can contribute to the development of bronchopulmonary complications. Currently, there is a wide variety of microorganisms inhabiting the respiratory tract of patients with tuberculosis of the respiratory system, while markers of pulmonary dysbiosis have not been established. Changes in the microbiota of the respiratory system depend on a number of factors: the presence/absence of bacterial release, sensitivity/resistance of the causative agent of tuberculosis to antibacterial drugs, chemotherapy regimen, etc. Conclusion. The composition of the microbiota of the respiratory tract in patients with tuberculosis of the respiratory system has not been studied enough. The available research is fragmented and not conceptual in nature. However, epidemiological realities (pandemics, the presence of tuberculosis–endemic countries and regions, the trend towards an increase in drug-resistant forms of tuberculosis, the high incidence of bronchopulmonary pathology of non-specific etiology in patients with pulmonary tuberculosis) necessitate representative studies on this topic.